Green innovation: a multidomain systematic review - Oduro, Stephen; Maccario, Guglielmo; De Nisco, Alessandro (European journal of innovation management, 2022)
PurposeThis paper examines the status and evolution of green innovation research from 1948 to 2018.Design/methodology/approachUsing a systematic review of 293 peer-reviewed scholarly articles, the authors classify journal outlets, publication trends, research methods (research type, approach, design), themes/topics focus, country and regional distribution and theoretical perspectives, identifying main trends. They apply mixed methodologies, integrating both content and descriptive analyses.FindingsResults reveal the following critical conclusions: (1) publication trends disclose a steady growth of interest in green innovation research in the last decade (2011–2018), with most of the articles appearing in top-ranked journal outlets; (2) empirical studies involving quantitative surveys dominate the field over other methods like experiments, case studies (qualitative) and conceptual models; (3) research themes/topics are multi-perspectives, covering management and strategic dimension of green innovation (e.g. green innovation integration and adoption strategy; collaboration and networking in green innovation; green innovation management systems, green supply chain management, etc.), performance (financial, non-financial and both), drivers/antecedents and consumer green behavior; however, the “management and strategy” papers are by far higher; (4) studies are preponderately multi-country focused, concentrated in Europe and Australasia, with a low concentration in emerging markets like Africa and South America; And (5) the field lacks the adoption and development of novel theories. So far, the research fields principally focus on the “Porter hypothesis” and resource-based view in terms of the theory-driven studies. Based on these findings, knowledge gaps are identified, as are limitations and actionable agenda for future research.Originality/valueAs the first systematic review to adopt a comprehensive, holistic approach in synthesizing and summarizing research vis-à-vis the phenomenon of green innovation, the study offers practitioners and researchers an insightful understanding of the relevant issues that have been investigated on green innovation, thereby anchoring the evolutions for further sustainable-oriented research and improvement in management practices.